Effect of Primary Tumor Location on Second- or Later-Line Treatment With Anti-Epidermal Growth Factor Receptor Antibodies in Patients With Metastatic Colorectal Cancer: A Retrospective Multi-Center Study - Archwamety, Anita; Teeyapun, Nattaya; Siripoon, Teerada; Poungvarin, Naravat; Tanasanvimon, Suebpong; Sirachainan, Ekaphop; Akewanlop, Charuwan; Korphaisarn, Krittiya (Frontiers in Oncology, 2022)
Background: Current guidelines recommend anti-epidermal growth factor receptor monoclonal antibodies (anti-EGFR Ab) as first-line treatment only in patients with left-sided RAS wild type (RASwt) metastatic colorectal cancer (mCRC). However, there are no guideline recommendations specific to tumor sidedness in subsequent-line treatment. This study aimed to investigate the effect of primary tumor location on second- or later-line treatment outcomes in patients with KRASwt mCRC. Methods: Medical records of patients diagnosed with mCRC at 3 academic centers in Thailand (Siriraj, Chulalongkorn, and Ramathibodi hospital) between 2008 and 2019 were retrospectively reviewed. Patients with KRASwt mCRC who received anti-EGFR Ab in second- or later-line treatment were included. The impact of tumor sidedness on progression-free survival (PFS) was determined using Kaplan-Meier method, and those results were compared using log-rank test. Results: Among the 2,102 patients who had KRAS analysis data, 1130 (54%) patients had KRASwt. Of those, 413 patients received anti-EGFR Ab in second- or later-line treatment. One hundred and sixty-two of 413 (39%) patients had extended RAS analysis. Seventy (17%) patients had right-sided tumors. Two hundred and thirty-eight (58%) patients received anti-EGFR Ab in the third line, and 132 (32%) patients and 43 (10%) patients were treated in the second and more than third line, respectively. Single-agent irinotecan was the most commonly used backbone chemotherapy (303/413, 73%). Patients with right-sided tumors had non-significantly inferior PFS compared to patients with left-sided tumors (median PFS: 5.7 months (mo), 95% confidence interval [CI]: 3.9-7.5 vs. 7.5 mo, 95% CI 6.5-8.5; p=0.17). Subgroup analysis showed no difference in PFS when stratified by treatment lines. Patient with right-sided tumors had significantly inferior OS compared to patients with left-sided tumors (median OS: 23.3 mo vs. 29.9 mo; p=0.005). Conclusions: To date, this is the largest real world data of the effect of primary tumor location on anti-EGFR Ab which demonstrated that tumor sidedness has no significant impact on treatment outcomes in KRASwt mCRC patients receiving second- or later-line therapy. Our findings do not support the utility of tumor sidedness for treatment selection in these settings. We confirmed that patients with right-sided tumors had significantly worse survival.